2022
DOI: 10.1002/ange.202201491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Doped Highly Graphitic Carbon Urchin‐Like Hollow Structures Loaded with Single‐Ni Atoms towards Efficient CO2Electroreduction

Abstract: The rational design of single-atom catalysts featuring excellent conductivity, highly accessible discrete active sites and favorable mass transfer is crucial for electrocatalysis but remains challenging. In this study, a reliable Ni-catalyzed and Ni-templated strategy is developed to synthesize a single-atom catalyst by transforming metallic Ni into single-Ni atoms anchored on hollow porous urchin-like (HPU) N-doped carbon (NC) (designated as Ni-NC(HPU)), which possesses high crystallinity and sufficient Ni-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The Ni 2p XPS spectrum in Figure 3C showed that the binding energy of Ni 2p 3/2 and Ni 2p 1/2 peaks in Ni‐SAC‐NA centered at 854.6 eV and 872.0 eV, respectively. Accompanied by two obvious satellite peaks, it suggested an oxidized state of Ni δ+ species in Ni‐SAC‐NA samples (0 < δ < 2) 38,39 . The high‐resolution XPS of N 1s for Ni‐SAC‐NA (Figure 3D) can be well fitted into four characteristic peaks located at 398.6 eV, 399.1 eV, 400.2 eV, and 401.3 eV, which corresponded to pyridinic‐N, Ni‐N x , pyrrolic‐N and graphitic‐N, respectively 39 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Ni 2p XPS spectrum in Figure 3C showed that the binding energy of Ni 2p 3/2 and Ni 2p 1/2 peaks in Ni‐SAC‐NA centered at 854.6 eV and 872.0 eV, respectively. Accompanied by two obvious satellite peaks, it suggested an oxidized state of Ni δ+ species in Ni‐SAC‐NA samples (0 < δ < 2) 38,39 . The high‐resolution XPS of N 1s for Ni‐SAC‐NA (Figure 3D) can be well fitted into four characteristic peaks located at 398.6 eV, 399.1 eV, 400.2 eV, and 401.3 eV, which corresponded to pyridinic‐N, Ni‐N x , pyrrolic‐N and graphitic‐N, respectively 39 .…”
Section: Resultsmentioning
confidence: 91%
“…Accompanied by two obvious satellite peaks, it suggested an oxidized state of Ni δ+ species in Ni‐SAC‐NA samples (0 < δ < 2) 38,39 . The high‐resolution XPS of N 1s for Ni‐SAC‐NA (Figure 3D) can be well fitted into four characteristic peaks located at 398.6 eV, 399.1 eV, 400.2 eV, and 401.3 eV, which corresponded to pyridinic‐N, Ni‐N x , pyrrolic‐N and graphitic‐N, respectively 39 . The Ni‐N x moiety also suggested that Ni species were stabilized by N sites.…”
Section: Resultsmentioning
confidence: 91%
“…X-ray photoelectron spectroscopy (XPS) was employed to study the chemical states and composition of the catalysts. The Ni 2p spectra of both NiNCNT and NiNCNT-H present a sharp Ni 2p 3/2 peak at 854.7 eV (Figures a and S7a), which is approximately 1.7 eV lower than that of Ni 2+ in NiCNT (856.4 eV) (Figure S8) due to Ni 0 oxidation upon exposure to air, suggesting a low-valent state of Ni δ+ (0 < δ < 2) species in NiNCNT and NiNCNT-H. , The N 1s spectra of NiNCNT (Figure b) and NiNCNT-H (Figure S7b) show similar pyridinic N (398.3 eV), Ni–N (399.2 eV), pyrrolic N (400.4 eV), graphitic N (401.3 eV), and oxidized N (405.7 eV) peaks, , indicating the presence of the Ni–N–C structure. The surface Ni content in NiNCNT determined by XPS is 1.56 atom %, which decreases to 0.71 atom % after heated acid treatment, confirming the significant removal of Ni nanoclusters in NiNCNT-H.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by these significant advances, incorporating S into Pd to form the amorphous PdS x might produce high-valence Pd with rich coordination-unsaturated isolated Pd sites. Additionally, compared with bulk and solid counterparts, hollow nanostructured materials can improve electrochemical performance by their large surface area and facile electron/mass transfer. Thus, we speculate that amorphous PdS x nanocapsules (PdS x ANCs) with isolated Pd sites can induce σ-alkynyl adsorption and increase the physical distance from other functional groups to the catalyst’s surface, then enabling the efficient semihydrogenation of functionalized terminal alkynes with the retention of easily reducible groups and strongly coordinated skeletons. A preliminary density functional theory (DFT) calculation shows that phenylacetylene, a model substrate, preferentially adsorbs on the surface of Pd via flat coadsorption of a benzene ring and an alkynyl group, but the adsorption mode at an uncertain angle only via the terminal of the alkynyl group is more favorable on the surface of PdS that owns isolated Pd sites with Pd–S bonds (Figure S1), rationalizing our assumption of the specific adsorption of terminal alkynes.…”
Section: Results and Discussionmentioning
confidence: 99%